Pelatihan Dasar Bahasa Pemrograman C Pada Siswa SMK Muhammadiyah Parakan , Tangerang Selatan - Simon Simarmata; Tedi Purwanto; Jamaluddin (CV. Multi Kreasi Media, 2025)
Programming is the process of creating instructions that a computer can execute to perform a specific task. Imagine a robot that can perform simple tasks, such as picking up a toy or drawing a picture. To make the robot perform these tasks, we need to provide clear and systematic instructions. Programming is the process of creating these instructions so that the computer or robot can understand and execute them. These instructions are called code or programs. Programming is very important in the world of work because it can open up broad career opportunities and improve problem-solving skills. By learning programming, we can build applications, websites, games, or tools that can be used by others, thus opening the door to creative expression and in-depth technological learning. This is what motivated us, lecturers from the Informatics Engineering Study Program at Pamulang University, to try to share knowledge and experience with students of SMK Muhammadiyah Parakan, a private school located in Pondok Benda Pamulang, South Tangerang. The presence of this training is to increase students' knowledge and interest in learning more about programming. This training is expected to broaden students' horizons and increase their interest in the importance of computer technology, especially in programming. The community service program, conducted by lecturers from the Faculty of Computer Science, Informatics Engineering Study Program, Pamulang University, is entitled